2017
DOI: 10.1177/0284185117729185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vascular invasion in patients with musculoskeletal tumors of lower extremities: use of time-resolved 3D MR angiography at 3-T

Abstract: Background Time-resolved angiography with stochastic trajectories (TWIST) sequence makes considerable progress in temporal and spatial resolution, which presents high potential in evaluation of vascular diseases. Purpose To assess magnetic resonance imaging (MRI) using TWIST MR angiography (MRA) sequence in the assessment of vascular invasion for bone and soft-tissue tumors in comparison to computed tomography angiography (CTA) as the reference standard. Material and Methods Thirty-three patients with lower ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Jin et al assessed the role of TWIST MR angiography to evaluate the vascular invasion in musculoskeletal tumors of lower extremities and found out that it reliably delineates the vascular involvement. 9 Armstrong et al evaluated the role of TWIST MRA in helping to image the complex central venous accesses and concluded that it can reliably identify the candidate sites for the venous catheter insertion. 10 Korn et al found double bolus injection TWIST-MRA helps the evaluation of cervical arteries with the elimination of venous contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al assessed the role of TWIST MR angiography to evaluate the vascular invasion in musculoskeletal tumors of lower extremities and found out that it reliably delineates the vascular involvement. 9 Armstrong et al evaluated the role of TWIST MRA in helping to image the complex central venous accesses and concluded that it can reliably identify the candidate sites for the venous catheter insertion. 10 Korn et al found double bolus injection TWIST-MRA helps the evaluation of cervical arteries with the elimination of venous contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s, there was an interest in angiography in extremity trauma (49,50) and in 1982, a comparison with CT was published (51). With improved angiographic techniques, there was a renewed interest in tumor imaging at the end of the 20th century (52) and angiography migrated from conventional catheter techniques towards CT (53,54) and MR (55) angiography in tumor evaluation.…”
Section: Techniquesmentioning
confidence: 99%
“…Soft tissue mass of leg usually invades adjacent vessels and nerves. 1,2 Computed tomography angiography (CTA) is the rst-line test in revealing arterial invasion by tumor. 2 Magnetic resonance angiography (MRA) serves as an alternative to CTA.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Computed tomography angiography (CTA) is the rst-line test in revealing arterial invasion by tumor. 2 Magnetic resonance angiography (MRA) serves as an alternative to CTA. 2 However, CTA and MRA have di culty in identifying nerve invasion by tumor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation